Exploring the value management critical success factors for sustainable residential building – A structural equation modelling approach. (15th April 2021) - Kineber, Ahmed Farouk; Othman, Idris; Oke, Ayodeji Emmanuel; Chileshe, Nicholas; Zayed, Tarek
Abstract: Sustainability principles should be implemented during all the phases of the decision-making process of constructing residential buildings to achieve maximum gains without compromising the function of such projects. This study identified and examined the critical success factors (CSFs) required for implementing value management (VM) in residential building projects. With a view to the sustainability of such the projects. The CSFs for VM were identified from previous studies, which were then contextually adjusted using both semi-structured interviews and a pilot study via the Exploratory Factor Analysis (EFA) technique. The EFA results showed that the VM CSFs could be categorized into four constructs: stakeholders and knowledge, culture and environment, workshop dynamics, and standardization. Questionnaires were then administered to 214 building stakeholders within the Egyptian building industry. Partial least square structural equation modelling (PLS-SEM) was used to develop the CSFs model. Despite that Egyptian professionals with limited practice experiences were quite knowledgeable about VM, results showed that stakeholders and knowledge were crucial CSFs for implementing VM. The results of this study will be a guide for decision-makers to reduce costs and improve sustainability by introducing VMs in the Egyptian construction industry. Highlights: Partial least squares-structural equation models (PLS-SEM) for predicting the impact of critical success factors (CSFs) for value management (VM) were validated. The VM knowledge and awareness among Egyptian residential building practitioners are in a moderate to a high level. Established that most Egyptian residential building practitioners did not practice VM in their projects. Stakeholders and knowledge, culture and environment, workshop dynamics, and standardization identified as CSFs for VM. The proposed PLS-SEM model priorities the VM CSFs and Offering VM implementation "road map" for sustainable residential building success.